Integrasi Software Simulasi Dalam Proses Bisnis Hulu Minyak Untuk Optimasi Aset Perpipaan - Putra, Mario Frana; Widjaja, Tri (Syntax Corporation, 2025)
This study aims to evaluate the integration of the PIPELINE SIMULATOR software into the decision-making process for pipeline asset development. The methods applied include multi-criteria analysis using the Analytical Hierarchy Process (AHP) to determine the best development scenario alternatives, Business Model Canvas (BMC) analysis to assess the strategic impact of simulation software on business processes, and economic analysis to evaluate the financial feasibility of the proposed scenarios. Three technical design alternatives are analyzed through simulation: constructing a new pipeline, optimizing existing pipelines by shutting down older wells, and reinforcing existing pipelines using pipe sleeving. Evaluations are based on five key criteria: cost, safety, reliability, maintainability, and environmental impact. The simulation results indicate that each alternative presents distinct advantages. The scenario involving the addition of a new pipeline offers the most balanced performance in terms of technical reliability, operational sustainability, and investment support. The well decommissioning scenario demonstrates cost efficiency, while the pipe sleeving approach is constrained by technical limitations and greater operational risks. The integration of simulation software also delivers strategic value to business processes by improving technical planning efficiency, strengthening cross-functional collaboration, and supporting digital transformation. Therefore, the implementation of PIPELINE SIMULATOR is recommended as part of the standard procedure in pipeline development project submissions within upstream oil and gas companies.